GnRH agonist triggering followed by 1500 IU of HCG 48 h after oocyte retrieval for luteal phase support. Issue 5 (November 2020) - Kol, Shahar; Segal, Linoy
Abstract: Research question: Gonadotrophin releasing hormone (GnRH) agonist trigger after GnRH antagonist-based ovarian stimulation protocol for IVF is gaining popularity, because it prevents ovarian hyperstimulation syndrome and allows for near physiological LH and FSH surges. A small dose of HCG (1500 IU) on the day of oocyte retrieval, followed by daily progesterone administration, is currently the preferred way to secure adequate luteal support after GnRH agonist trigger. In the present study, the possibility that a bolus of 1500 IU HCG, given 2 days after oocyte retrieval, may be sufficient to sustain adequate luteal support without additional progesterone treatment was questioned. Design: A non-interventional retrospective cohort study between conducted between April 2017 and August 2018. A total of 154 consecutive patients treated with GnRH agonist trigger followed by day-2 HCG (1500 IU) support only (study group) were included. Data were compared with 155 consecutive patients who were treated with HCG (6500 IU) trigger followed by conventional progesterone luteal support (control group). Results: Pregnancy, miscarriage and live birth rates were comparable between the study and control groups. In patients who became pregnant, mean oestradiol level 14 days after oocyte retrieval was 4719 pmol/l and 2672 pmol/l in the study and control group, respectively ( P < 0.001), reflecting robust luteal activity in the study group. Conclusions: A bolus of 1500 IU HCG, administered 2 days after retrieval, can provide excellent luteal support, without the need for further progesterone supplementation.